2013
DOI: 10.4081/or.2013.e26
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of arthroscopic placement of autologous matrix-induced chondrogenesis grafts in the cadaver hip joint

Abstract: An assortment of clinical trials have been done presenting the effectiveness of autologous matrix-induced chondrogenesis (AMIC) for the regeneration of chondral leasions. The purpose of the study was to underline the accessability of the acetabulum and the femoral head through the known portals and prove i) the feasibility of placing the AMIC in the different zones of the hip joint and ii) check for dislocation after joint movement. Six human cadavers underwent hip arthroscopy on both hips. Two chondral lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
1
Order By: Relevance
“…The injectable autologous chondrocyte implantation resembles a new treatment option. As there is no need for a scaffold material, it offers a technically less demanding arthroscopic option without the risk of a dislocation of the scaffold material [15, 35]. Early studies could show the feasibility of this procedure in the setting of hip arthroscopy [16, 17] and short-term results have been promising [18, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injectable autologous chondrocyte implantation resembles a new treatment option. As there is no need for a scaffold material, it offers a technically less demanding arthroscopic option without the risk of a dislocation of the scaffold material [15, 35]. Early studies could show the feasibility of this procedure in the setting of hip arthroscopy [16, 17] and short-term results have been promising [18, 36].…”
Section: Discussionmentioning
confidence: 99%
“…With the good long-term results of ACI in knee surgery the technique has been transferred to the hip for the treatment of acetabular cartilage defects. First investigations showed excellent results of the ACI procedure using scaffold material in the hip [13, 14], but the use of a scaffold is technically demanding in the concave acetabulum and has the risk of a scaffold dislocation [15]. Therefore, scaffold free matrix-associated injectable agents have been developed with the potential of an easier and less invasive implantation process.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold implantations are technically demanding to stabilize on the concave acetabulum, and therefore, chondrocytes may displace overtime, leading to poorer outcomes. [31] To overcome this problem, some authors have used chondrocytes attached to adhesive spheres or gels that are injected directly into the cartilage deficient surface. A study of 32 hips treated with chondrocytes embedded in injected gels with a 3-year followup concluded that this method was suitable for large defects in weight-bearing zones.…”
Section: Management Of Articular Cartilage Injuriesmentioning
confidence: 99%
“…Das häufig auch als AMIC ® bezeichnete Verfahren (autologe matrixinduzierte Chondrogenese), erfordert bei Anwendung im Hüftgelenk eine hohe operative Geschicklichkeit, speziell für die korrekte Größenkonfektionierung und arthroskopische Fixierung des Biomaterials. Außerdem besteht am Hüftkopf die relevante Gefahr einer Implantatabscherung [37]. Weitere technische Durchführungsempfehlungen sind im aktuellen Praxisleitfaden der AG Geweberegeneration der DGOU im entsprechenden Kapitel zum Hüftgelenk beschrieben [12].…”
Section: Voraussetzungen Und Unterschiedliche Verfahren Für Die Biolounclassified